2021
DOI: 10.1097/md.0000000000028460
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of influenza A viruses among patients hospitalized for severe acute respiratory infection in a tertiary care hospital in Romania in the 2018/19 season

Abstract: The seasonal circulation of influenza viruses and the impact that this infection has on the population varies from year to year. We have prospectively captured hospital-based surveillance data describing the circulation of influenza viruses and characterizing patients with influenza admitted to a tertiary hospital in Bucharest, Romania in the 2018/19 season. We have conducted an observational descriptive epidemiological study analyzing all consecutive patients hospitalized for influenza like illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Influenza vaccination is notoriously safe and is associated with acceptable levels of immunogenicity among patients with HIV infection [ 19 , 20 ]. However, in Romania, vaccination rates among this patient population remain generally low, and influenza-related hospitalizations and deaths among patients with HIV infection are reported annually [ 21 , 22 ]. Similarly, SARS-CoV-2 vaccination [ 23 ] and pneumococcal vaccination [ 24 ] have been shown to be safe and to display acceptable efficacy among patients with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccination is notoriously safe and is associated with acceptable levels of immunogenicity among patients with HIV infection [ 19 , 20 ]. However, in Romania, vaccination rates among this patient population remain generally low, and influenza-related hospitalizations and deaths among patients with HIV infection are reported annually [ 21 , 22 ]. Similarly, SARS-CoV-2 vaccination [ 23 ] and pneumococcal vaccination [ 24 ] have been shown to be safe and to display acceptable efficacy among patients with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, primary care physicians play a pivotal role in providing free flu vaccinations to individuals in high-risk groups, a practice also observed in Romania. 5 Recognizing the convenience and widespread accessibility of pharmacists, an evolving strategy aims to strengthen vaccination efforts by integrating them as administrators. This shift has demonstrated efficacy in augmenting coverage rates, supported by empirical evidence showcasing pharmacists’ contributions to safeguarding those susceptible to the flu.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Shi et al [29] showed peaks of Influenza A -H3N2 for four years in a row in northern China; however, at the peak of the flu in 2015-2016, this subtype circulated together with influenza A-H1N1, already in southern China, and the predominant virus was the A-H3N2 subtype. On the other hand, in the studies by Araújo et al carried out in the state of Goiás [28], and in a study by Drăgănescu et al carried out in Romania [30], the predominant etiology was the A-H1N1 virus. In mainland China, the influenza B virus (mainly the B-Victoria subtype) was identified as circulating in all years between 2005-2016, but with lower activity than influenza A [31].…”
mentioning
confidence: 99%